THE IMPORTANCE OF STEAM TECHNOLOGIES IN IMPROVING STUDENTS’ PROFESSIONAL SPEECH COMPETENCE IN ENGLISH CLASSES - Umida Raimjanovna Irgasheva; Alijonova Iroda Botirjonovna (Лучшие интеллектуальные исследования, 2024)
Annotation: This article proves the importance of improving students’ professional speech competence based on STEAM technologies in teaching English. The basis of modern approaches, the suggestions and recommendations for enhancing the information-methodological support for the development of communicative, linguistic, sociolinguistic, pragmatic, speech and lexical competences with the help of STEAM technologies in teaching English are explained in the article.